1999
DOI: 10.1074/jbc.274.16.11060
|View full text |Cite
|
Sign up to set email alerts
|

Human Acyl-CoA:Cholesterol Acyltransferase-1 (ACAT-1) Gene Organization and Evidence That the 4.3-Kilobase ACAT-1 mRNA Is Produced from Two Different Chromosomes

Abstract: . The human ACAT-1 cDNA was cloned by a somatic cell and molecular genetic approach. Chinese hamster ovary (CHO) cell mutants lacking ACAT activity (including clone AC29) were isolated (8); subsequent stable transfection experiments showed that human genomic DNAs complemented the ACAT deficiency in AC29 cells (9). A 1.2-kb human genomic DNA fragment was cloned from the stable transfectants. This fragment (designated as G2 DNA) led to the eventual cloning of a full-length human ACAT cDNA K1 (4011 bp in length).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
128
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 50 publications
2
128
0
Order By: Relevance
“…Trans-splicing refers to the recombination of sequences from two independently transcribed pre-mRNAs to form a composite mRNA. [1][2][3][4][5][6][7][8][9] We are developing a technology called spliceosome mediated RNA trans-splicing (SMaRT) to take advantage of the cell's endogenous splicing machinery as a strategy for modifying pre-mRNA. 10 The SMaRT process uses pretherapeutic RNA molecules (PTMs) that are designed to base pair with the intron of a targeted pre-mRNA to suppress target cis-splicing while enhancing trans-splicing between the PTM and target.…”
Section: Introductionmentioning
confidence: 99%
“…Trans-splicing refers to the recombination of sequences from two independently transcribed pre-mRNAs to form a composite mRNA. [1][2][3][4][5][6][7][8][9] We are developing a technology called spliceosome mediated RNA trans-splicing (SMaRT) to take advantage of the cell's endogenous splicing machinery as a strategy for modifying pre-mRNA. 10 The SMaRT process uses pretherapeutic RNA molecules (PTMs) that are designed to base pair with the intron of a targeted pre-mRNA to suppress target cis-splicing while enhancing trans-splicing between the PTM and target.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a newly developed, natural splicing reaction (that is thought to involve unconventional splicing) might play a role in the expression of some mammalian genes, when performed in combination with the cis-splicing process (Akopian et al, 1999;Breen and Ashcroft, 1997;Caudevilla et al, 1998;Kawasaki et al, 1999;Li et al, 1999;Shimizu and Honjo, 1993;Sullivan et al, 1991;Vellard et al, 1992;Zaphiropoulos, 1999;Frantz et al, 1999). One example is rat carnitine octanoyltransferase (COT) pre-mRNA, which undergoes a natural trans-splicing process that yields three COT mRNAs: one with a duplication of the COT E2 exon (....E2-E2...); a second with a duplication of the COT E2-E3 exons (...E2-E3-E2-E3...) and a third with no exon duplication.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the canonical SL-type trans splicing, which is a prerequisite for generating all mature mRNAs in trypanosomes, different variations of trans splicing patterns have been described in higher eukaryotes ( Figure 1): (1) intragenic trans splicing, in which two identical pre-mRNA molecules from the same gene are spliced together to generate an mRNA with duplicated exon sequences; (2) intergenic trans splicing, whereby an mRNA is generated from two pre-mRNAs that are derived from different genes, which can be located even on different chromosomes (interchromosomal trans splicing). A relatively well-characterized example for the latter case is the human ACAT1 gene, as previously described by Bo-Liang Li and colleagues [8]; importantly, characterization of trans splicing has not only been performed at the mRNA level, as in many other studies, but also been extended to the protein level and the effects on biochemical activities. In this case, exons of the ACAT1 mRNA are transcribed from two different chromosomes, namely 1 and 7, and the resulting 4.3-kb human ACAT1 mRNA encodes two functional protein isoforms (50-and 56-kDa in size) with differential enzymatic activities [8].…”
mentioning
confidence: 99%
“…A relatively well-characterized example for the latter case is the human ACAT1 gene, as previously described by Bo-Liang Li and colleagues [8]; importantly, characterization of trans splicing has not only been performed at the mRNA level, as in many other studies, but also been extended to the protein level and the effects on biochemical activities. In this case, exons of the ACAT1 mRNA are transcribed from two different chromosomes, namely 1 and 7, and the resulting 4.3-kb human ACAT1 mRNA encodes two functional protein isoforms (50-and 56-kDa in size) with differential enzymatic activities [8]. Now, Hu et al [1] continued their molecular analyses of ACAT1 trans splicing en detail by combining the characterization of both mRNA and protein products of ACAT1.…”
mentioning
confidence: 99%
See 1 more Smart Citation